2022
DOI: 10.1186/s12968-022-00877-x
|View full text |Cite
|
Sign up to set email alerts
|

Le CÅ“ur en Sabot: shape associations with adverse events in repaired tetralogy of Fallot

Abstract: Background Maladaptive remodelling mechanisms occur in patients with repaired tetralogy of Fallot (rToF) resulting in a cycle of metabolic and structural changes. Biventricular shape analysis may indicate mechanisms associated with adverse events independent of pulmonary regurgitant volume index (PRVI). We aimed to determine novel remodelling patterns associated with adverse events in patients with rToF using shape and function analysis. Methods Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Recently, attention has been drawn to RV geometric shape, which has been associated with exercise capacity, decrease in RV function and adverse events ( 23 , 24 ). Wall stress is strongly depended on geometry.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, attention has been drawn to RV geometric shape, which has been associated with exercise capacity, decrease in RV function and adverse events ( 23 , 24 ). Wall stress is strongly depended on geometry.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in computational medicine have enabled more quantitative approaches to characterizing ventricular shape and remodeling in individuals with heart disease. One such approach is the use of cardiac shape modeling to condense complex, multi-dimensional data from standard of care cardiovascular magnetic resonance (CMR) images into statistical atlases of cardiac structure and function [ 1 13 ]. These atlases are composed of interpretable shape and wall motion features that can be important quantitative biomarkers of patient status and outcome and, in turn, aid in prognosis and treatment of disease.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, cardiovascular computational modeling has now reached maturity, providing access to new biomarkers, 8 , 9 while statistical models—atlases of the heart—have demonstrated the importance of shape in the diagnosis of cardiovascular disease. 10 , 11 Specifically, comprehensive automated atrial remodeling assessment has previously demonstrated a predictive value for reoccurrence of atrial fibrillation (AF) following pulmonary vein (PV) ablation. 12 These postprocessing analyses can be used on widely available routinely acquired balanced steady-state free-precession cine sequences at rest.…”
mentioning
confidence: 99%